Postsurgical Inflammation as a Causative Mechanism of Venous Thromboembolism - Albayati, Mostafa A.; Grover, Steven P.; Saha, Prakash; Lwaleed, Bashir A.; Modarai, Bijan; Smith, Alberto (Seminars in Thrombosis and Hemostasis, 2015)
Surgery is associated with an increased risk of venous thromboembolic events (VTE) including deep vein thrombosis and pulmonary embolism. Although the current treatment regiments such as mechanical manipulation and administration of pharmacological prophylaxis significantly reduced the incidence of postsurgical VTE, they remain a major cause of postoperative morbidity and mortality worldwide. The pathophysiology of venous thrombosis traditionally emphasizes the series of factors that constitute Virchow triad of factors. However, inflammation can also be a part of this by giving rise to a hypercoagulable state and endothelial damage. The inflammatory response after surgery, which is initiated by a cytokine “storm” and occurs within hours of surgery, creates a prothrombotic environment that is further accentuated by several cellular processes including neutrophil extracellular traps formation, platelet activation, and the generation of tissue factor–bearing microparticles. Although such inflammatory markers are elevated in undergoing surgery, the precise mechanism by which they give rise to venous thrombosis is poorly understood. Here, we discuss the potential mechanisms linking inflammation to thrombosis, and highlight strategies that may minimize surgical inflammation and reduce the incidence of postoperative VTE.
Keywords: surgery; inflammation; thromboembolism